2017
DOI: 10.1177/1077699017712991
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Partisan Media Effects in the 2014 U.S. Midterm Elections

Abstract: This study tested partisan media effects in the 2014 U.S. midterm elections. A survey was distributed to 992 residents of Georgia, Iowa, and North Carolina. A novel multigroup latent variable structural equation model tested the direct, indirect, and conditional effects of political interest, partisan media use, political information efficacy, and partisanship on affective polarization. Findings demonstrated a polarizing effect of pro-partisan media, a depolarizing effect of cross-cutting media, and an indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
2
6
0
1
Order By: Relevance
“…Political animus was measured using the feeling thermometer ratings commonly used in political communication research on polarization (e.g., Garrett et al, 2014; Iyengar et al, 2012; Warner, 2017). Following the recommendations of Druckman and Levendusky (2019), we asked participants about members (supporters) of political parties rather than about the parties themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Political animus was measured using the feeling thermometer ratings commonly used in political communication research on polarization (e.g., Garrett et al, 2014; Iyengar et al, 2012; Warner, 2017). Following the recommendations of Druckman and Levendusky (2019), we asked participants about members (supporters) of political parties rather than about the parties themselves.…”
Section: Methodsmentioning
confidence: 99%
“…This finding supports prior political communication research showing that debates have more upside than downside for candidates (Blais & Perrella, 2008;. In fact, debates often lead to more increases in ingroup candidate evaluations than decreases in out-group candidate evaluations (Warner et al, 2018). Similar findings were observed here, with positive changes for in-group evaluations having a greater effect size than negative changes for out-group candidate evaluations.…”
Section: Political Brandingsupporting
confidence: 90%
“…The results were strongest for out-group negative associations, a sign of negative partisanship (Iyengar et al, 2012;Mason, 2018), although nationalized involvement also generated more positive in-group associations as well. These results echo a study by Warner (2018), who found that the use of national partisan media promoted in-group increases and out-group decreases in candidate favorability during a mid-term Senate campaign (p. 13). In my study, feelings of national involvement did the same with candidate thoughts.…”
Section: Involvementsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it was unclear in what direction political interest and affective polarization would influence partisan effects on EU attitudes. Political interest has been shown to increase news consumption from both pro‐partisan and cross‐cutting media in US context (Warner, 2018). We hypothesized that EU attitudes are influenced by traditional worldviews, but also interpret it as the social manifestation of a novel ideological cleavage (conceptually separate from the traditional left‐right division).…”
Section: The Roots Of Euroscepticism: Theoretical Framework and Hypot...mentioning
confidence: 99%